2017
DOI: 10.1038/onc.2017.103
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic inhibitors accentuate the anti-tumoral effect of HDAC5 inhibition

Abstract: The US FDA approval of broad-spectrum histone deacetylase (HDAC) inhibitors has firmly laid the cancer community to explore HDAC inhibition as a therapeutic approach for cancer treatment. Hitting one HDAC member could yield clinical benefit but this required a complete understanding of the functions of the different HDAC members. Here we explored the consequences of specific HDAC5 inhibition in cancer cells. We demonstrated that HDAC5 inhibition induces an iron-dependent reactive oxygen species (ROS) productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Previous studies and our data from this study show that HDACIs, including droxinostat, induce cellular apoptosis leading to cancer cell death [ 28 , 34 , 35 ]. A recent report showed that the balance disruption of the anti- and pro-oxidant system might be involved in the cancer cell sensitivity of HDACIs [ 36 38 ]. For example, inhibition of HDAC5 increased mitochondrial iron-dependent ROS production in HeLa cells, resulting in apoptosis and autophagy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies and our data from this study show that HDACIs, including droxinostat, induce cellular apoptosis leading to cancer cell death [ 28 , 34 , 35 ]. A recent report showed that the balance disruption of the anti- and pro-oxidant system might be involved in the cancer cell sensitivity of HDACIs [ 36 38 ]. For example, inhibition of HDAC5 increased mitochondrial iron-dependent ROS production in HeLa cells, resulting in apoptosis and autophagy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that the balance disruption of the anti- and pro-oxidant system might be involved in the cancer cell sensitivity of HDACIs [ 36 38 ]. For example, inhibition of HDAC5 increased mitochondrial iron-dependent ROS production in HeLa cells, resulting in apoptosis and autophagy [ 38 ]. Panobionstat, a pan HDACI, reduced the viability of HeLa cells through induction of ROS [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 gives the five highest-weighted target probabilities in the LDA projection, where four of those targets have known links to toxicity. For example, the histone deacetylases 5 and 6 are the highest weighted targets, and each are currently exploited in cancer therapies [52, 53]. Additionally, normal function of the Glucagon-like peptide 1 receptor is required for cell proliferation and hence negative regulation can be linked to apoptosis [54].…”
Section: Resultsmentioning
confidence: 99%
“…6B). Similar effects in cancer cells include HDAC6 knockdown in pediatric acute myeloid leukemia cells, which enhances cytarabine-induced apoptosis [158-160] and the use of histone deacetylase inhibitors in combination with gemcitabine, which augments killing of pancreatic cancer cell lines [161-165] and HeLa cells [99].…”
Section: Resultsmentioning
confidence: 99%